Clinicians and the coronial system: ability of clinicians to recognise reportable deaths. Issue 6884 (17th April 1993) - Start, R D; Delargy-Aziz, Y; Dorries, C P; Silcocks, P B; Cotton, D W
Abstract : OBJECTIVE--To assess the ability of clinicians to recognise deaths which require referral to the coroner. DESIGN--Postal questionnaire consisting of 16 fictitious case histories, 14 of which contained a clear indication for referral to the coroner. SETTING--Large teaching hospital. Coroner's office. SUBJECTS--200 clinicians from general medical and surgical firms and senior staff of the local coroner's office (two coroner's officers and the two deputy coroners). MAIN OUTCOME MEASURES--Number of correct assessments on questionnaire. RESULTS--The mean recognition score for the clinicians was 9.11 (range 3-14) with no difference between the clinical grades. All of the coroner's senior staff recorded maximum recognition scores of 16. CONCLUSIONS--The study highlights several features of the coronial system which are poorly understood by clinicians and provides the basis for an initiative to improve the medicolegal education of all clinicians.